Carcinoma of the Colon in an Adult with Intestinal Malrotation. (29th July 2013) - Donaire, Michael; Mariadason, James; Stephens, Daniel; Pillarisetty, Sitaram; Wallack, Marc K.
Abstract : Colon cancer is the third most common cancer in the USA. Intestinal malrotation diagnosed in adulthood was, until recently, a very rare phenomenon. While patients may present with intestinal obstruction or abdominal pain, the diagnosis is now often made as an incidental finding by computed tomography (CT). Surprisingly we found only seven case reports of carcinoma of the colon in patients with malrotation; CT failed to make the preoperative diagnosis in a majority. Laparoscopic colon surgery is rapidly becoming standard of care for colon cancer. We present a case of carcinoma of the colon in an adult that thwarted attempts at laparoscopic resection due to failure to recognize malrotation preoperatively. The literature is reviewed, and the implications of malrotation in patients with colon cancer are examined.